Exploring student ideas about biological variation. Issue 12 (13th August 2019) - Alred, Ashley R.; Doherty, Jennifer H.; Hartley, Laurel M.; Harris, Cornelia B.; Dauer, Jenny M.
ABSTRACT: An understanding of biological variation is important for understanding ecological interactions, ecosystem function, and species' response to environmental change. Biological variation is essential to species survival because natural selection acts upon the phenotypic variation within a population: the more varied the population's genetic resources, the more likely that the population will persist into the future. We explored how students think about biological variation by evaluating written assessments and interviews of grades 6–16 students about starting a captive breeding programme for species conservation. We created a qualitative framework that describes levels of proficiency in student ideas about biological variation. Lower level responses reason about attributes related to an individual's reproduction and survival rather than population-level variability. Student responses at a middle level of sophistication point to the importance of variation but do not link it mechanistically to species survival and resilience. We also describe alternative conceptions related to biological variation and natural selection which exist at all grade levels. Educators can use these findings to inform curriculum and instruction in terms of addressing important concept areas (e.g. variation at the population scale) and some common alternative conceptions that may impact an accurate understanding of natural selection and evolution.